تكنولوجيا الاتصال ودورها في تنمية مهارات اللغة العربية من خلال نشاط فهم المنطوق السنة الخامسة إبتدائي أنموذجا - تجاني, أمينة; حسونة, حفيظة; خرشي, فايزة (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة الموسومة بـ "تكنولوجيا الاتصال ودورها في تنمية مهارات اللغة العربية من خلال نشاط فهم المنطوق -السنة الخامسة ابتدائي أنموذجا-" إلى التعرف على مدى تــأثير تكنولوجيا الاتصال في تنمية المهارات اللغوية (الاستماع، التحدث، القراءة، الكتابة) من خلال نشاط فهم المنطوق لدى تلاميذ السنة الخامسة. اشتملت الدراسة على جانب نظري وجانب تطبيقي واستخدمت الباحثتان المنهج الوصفي التحليلي، وقامتا بدراسة ميدانية تم فيها تقديم نشاط فهم المنطوق باستعمال القصص المصورة لأفراد العينة التجريبية واعتمدنا فيها على الملاحظة والاختبار لاستخلاص النتائج. تكوّن مجتمع الدراسة من 54 تلميذا في السنة الخامسة مقسمين على مجموعتين تجريبية في مدرسة زواري أحمد البشير بالوادي متكونة من (27 متعلما)، وأخرى ضابطة بمدرسة غريسي مصباح بالوادي (27 متعلما) في السنة الدراسية 2024/2025. وقد خلصت الدراسة إلى انه لتكنولوجيات الاتصال فاعلية كبيرة في تقديم نشاط فهم المنطوق وكذا تنمية المهارات اللغوية والتجاوب لمتعلمي الطور الابتدائي. This study, entitled “Communication Technology and its Role in Developing Arabic Language Skills through Spoken Understanding Activity - Fifth Year of Primary School as a Model,” aims to identify the extent of the impact of communication technology in developing language skills (listening, speaking, reading, writing) through Understanding Speech Activity. What is spoken among fifth-year students? The study included a theoretical aspect and an applied aspect. The two researchers used the descriptive and analytical approach, and they conducted a field study in which the activity of understanding the spoken language was presented using comic stories to the members of the experimental sample, and in it we relied on observation and testing to draw conclusions. The study population consisted of 54 students in the fifth year, divided into two experimental groups at the Zuari Ahmed Al-Bashir School in the Valley, consisting of (27 learners), and a control group at the Gresi Misbah School in the Valley (27 learners) in the academic year 2024/2025. The study concluded that communication technologies are highly effective in providing speech comprehension activities, as well as developing language skills and response to primary school learners.
لسانيات عامة
Keywords: تكنولوجيا الاتصال، تعليمية اللغة العربية، المهارات اللغوية، نشاط فهم المنطوق.; communication technology; educational Arabic language; language skills; spoken comprehension activity..